2018
DOI: 10.3390/ijerph15061288
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Perception of Social Support Among Rural Area Seniors—A Cross-Sectional Survey of Polish Population

Abstract: Introduction and objective: Social support constitutes an important determinant of an elderly person’s health and of functioning in his or her living environment. It depends on available support networks and the type of help received. Measurement of social support should encompass both its structure and the functions it fulfills, which enables detailed assessment of the phenomenon. The aim of the study was to compare the perception of social support among rural area seniors provided with institutional care wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Moreover, between the ages of 85+ years, we found a weak negative correlation (0.096) between LS and PSS but this correlation was also not significant (p = 0.480). While this study revealed that there was a positive correlation between LS and PSS among older person aged 75-84 years which has been supported in previous studies (Chruoeciel, et al, 2018;Ghimire, et al, 2018;Prakash & Srivastava 2020), there was a negative correlation between PSS and LS among seniors aged 85 years and older suggesting that those with high PSS scores tend to have low LS. While this relationship was not significant, contextual factors in Ekiti State such as large family size, poverty and unemployment of caregivers as well as the psychophysiological characteristics of those aged 85+ might have influenced this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, between the ages of 85+ years, we found a weak negative correlation (0.096) between LS and PSS but this correlation was also not significant (p = 0.480). While this study revealed that there was a positive correlation between LS and PSS among older person aged 75-84 years which has been supported in previous studies (Chruoeciel, et al, 2018;Ghimire, et al, 2018;Prakash & Srivastava 2020), there was a negative correlation between PSS and LS among seniors aged 85 years and older suggesting that those with high PSS scores tend to have low LS. While this relationship was not significant, contextual factors in Ekiti State such as large family size, poverty and unemployment of caregivers as well as the psychophysiological characteristics of those aged 85+ might have influenced this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Communal life in rural old-age care institutions can alleviate depression and improve the life satisfaction of the elderly [ 82 ]. However, in recent years, the existing social networks of residents in rural old-age care institutions have been significantly reduced in number and diversity, posing the risk of social isolation [ 21 , 83 , 84 ]. As a promising solution, long-distance mental consultation services can alleviate the problem of mental illness in rural nursing homes to some extent [ 85 ], with apparent advantages in saving both time and money [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…We expected that a high level of trust between entrepreneurs and their partners would enrich firms' knowledge-based resources. Trust is a central component of a social network [20,23,61]. Morgan and Hunt [62] found that trust within networks was key in helping focal firms cooperate with others and form interfirm alliances.…”
Section: Hypothesesmentioning
confidence: 99%